Determinants of further training: Evidence for Germany - Christian Grund; Johannes Martin (Institute for the Study of Labor (IZA), 2010)
Based on a German representative sample of employees we explore the relevance and development of further training in private sector firms. We focus on formal training and explore possible individual and job-based determinants of its incidence. We also show changes over time during a 20 year observation period from 1989 to 2008. Most hypotheses are supported by the empirical evidence. Job status and firm size are the most relevant characteristics for training participation. Furthermore, our analyses reveal a general trend of rising training rates from 1989 to 2008 indicating an increased importance in the German labor market.
Keywords: M53; 330; further training; GSOEP; human capital; panel data